Transactional Sex among Youths in Post-conflict Liberia - Atwood, Katherine A; Kennedy, Stephen B; Barbu, Ernlee M; Nagbe, Wede; Seekey, Wede; Sirleaf, Prince; Perry, Oretha; Martin, Roland B; Sosu, Fred (Journal of Health, Population and Nutrition, 2011)
This paper presents findings on sexual risk behaviours of Liberian youths based on five focus-group discussions conducted with 6th and 7th graders (n=36) attending an elementary/middle school in Monrovia, Liberia. The purpose of the focus-group discussions was to gain an understanding of the sexual behaviours of in-school Liberian adolescents. The focus-group discussions were part of a larger study to adapt an evidence- based HIV-prevention intervention—Making Proud Choices!—for in-school youths. Post-conflict conditions were discussed as a contributor to the emergence of high-risk sexual behaviours, including transactional sex, sexual violence, and lack of condom-use. Transactional sex was often described by the focus-group participants as occurring between young females and older, more financially-secure males to obtain cash, food, clothing, western commodities, and school-fees and was often encouraged by parents and promoted by peers. The findings also indicate that female adolescents make choices to engage in transactional sex to gain access to a continuum of material and consumer needs. These findings suggest that individual risk-taking behaviours are nested within complex sexual economies and that HIV-prevention interventions should be considered that leverage females’ agency and control. Key words: Acquired immunodeficiency syndrome; HIV; Sex behaviour; Transactional sex; Youth; Liberia DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7853 J HEALTH POPUL NUTR 2011 Apr;29(2):113-122